(untitled) (Journal of the College of Languages (JCL), 2016)
Abstract: Federico Garcia Lorca is considered in european and american literary circles as revolutionary symbol of contemporary literature writer through close association with the concerns of his country and the world, and also through the violent propensity to freedom, emancipation and innovation. This personal multi-talent has a significant impact in the spanish literary movement, in particularly, and in world, in general. If Lorca has andalusia blood, is no stranger to contemporary arab man to read to him, and contemplates his experience analyst and literary critic. This research is serious study of this character. There is no doubt the reader will put in front of many facts about personality of Lorca, facts have consideration and attention to study, analysis and evaluation. This paper is about the implications of social legacies and traditions that were maintained by the spanish society in the early twentieth century, also about the love and death in the production of theatrical spanish writer, Federico Garcia Lorca. We are studying in this article two dramas: (Blood Wedding = Bodas de sangre) and (House of Bernarda Alba = La casa de Bernada Alba) as models for study and analysis. Lorca is one of the writers who enriched the literary experience spanish and international with contents of authentic humanity transcends regional dimensions. Although the adhesion of Lorca in the village, the region and the tradition, was totally against the territorial by nature. His aim was to rise above Granada, the andalusian gypsy traditions, above Madrid, and over the whole of Spain.